2015
DOI: 10.3109/00016489.2015.1060628
|View full text |Cite
|
Sign up to set email alerts
|

Does age influence the success of intra-tympanic steroid treatment in idiopathic sudden deafness?

Abstract: PTA recorded before the beginning of the therapy (PTA_PRE) in group one was worse than for group two. In both groups the therapy was significantly effective in improving hearing thresholds, even if PTA_PRE was significant and negatively correlated with success rate. This effect disappeared within the population over 65. On average, each day of DELAY from the onset of hearing loss to the beginning of therapy cuts almost 2% of the possibility to recover. AGE was negative and significant when specified continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Attanasio et al also reported that each additional day of ITSI treatment delay following the onset of hearing loss reduces the possibility of recovery by an average of 2% to 3%. 5,18 From another perspective, our study also revealed that ITSIs can still be beneficial even if they are delayed by more than 4 weeks after symptom onset, as evidenced by the 17.8% hearing improvement rate achieved by patients who underwent ITSI treatment more than 4 weeks after symptom onset. The results for delayed treatment group were comparable with previous studies: Haynes et al 19 reported 15.79% of cases improved hearing after the delayed salvage ITSIs (time to injection >1 month), using the criteria of 20-dB gain in PTA.…”
Section: Discussionsupporting
confidence: 53%
“…Attanasio et al also reported that each additional day of ITSI treatment delay following the onset of hearing loss reduces the possibility of recovery by an average of 2% to 3%. 5,18 From another perspective, our study also revealed that ITSIs can still be beneficial even if they are delayed by more than 4 weeks after symptom onset, as evidenced by the 17.8% hearing improvement rate achieved by patients who underwent ITSI treatment more than 4 weeks after symptom onset. The results for delayed treatment group were comparable with previous studies: Haynes et al 19 reported 15.79% of cases improved hearing after the delayed salvage ITSIs (time to injection >1 month), using the criteria of 20-dB gain in PTA.…”
Section: Discussionsupporting
confidence: 53%
“…8 In earlier literature, older age in treated ISSNHL patients tends to be associated with a worse prognosis [12][13][14][15] or no change in hearing improvement. [16][17][18] One prospective, longitudinal cohort study of 127 ISSNHL patients found no significant difference in PTA recovery rates in the various age groups studied (30, 31-50, 51-70, 71 years old), but did note a trend in poorer results in the more extreme age groups (30, 71 years old) 19 Attanasio et al 20 found increased age was associated with worse hearing outcomes in their study of 496 patients; on subgroup analysis divided by age >65 years old, patients in the older subgroup had a statistically significant higher PTA both pre-and posttreatment.…”
Section: Discussionmentioning
confidence: 96%
“…However, there is no standard treatment for this disease due to the unclear etiology. 4 Thus, the clinical use of antiviral drugs, steroids, vasodilators, neurotrophic agents, and other drugs is an important choice for patients with sudden deafness.…”
Section: Introductionmentioning
confidence: 99%